Financial Budgets of Technology-Based SMEs From the Perspective of Sustainability and Big Data - Guobiao Zhang; Tao Wang (Frontiers Media S.A., 2022)
In this contemporary world, the words data and sustainability play a crucial role in determining the financial budgets of small and medium-sized enterprises (SMEs). Usually, it is stated that the survival of small and medium-sized enterprises (SMEs) is directly proportional to the growth and sustainability factor of the nation. The economic sustainability of a nation is dependent on appropriate functioning of SMEs. Any kind of direct impact on the working of SMEs will have its impact on the whole economy of a nation. There are different factors such as lack of financial capacity, low market demands, restrictions with regard to the capital, and barriers in the supply chain that affect the sustainability of SMEs worldwide. Nevertheless, small, and medium sized enterprises around the world are greatly investing on skills, innovation, and other capital related resources to mark up the demands of the external market. The main objective of this study is to examine the financial budgets of technology-based SMEs from the perspective of sustainability and big data. For this, the study collects data through a questionnaire from 1,800 Small and Medium Sized Enterprises. Based on a detailed and careful examination of the data, only 1,400 of the responses received were considered valid (79.75%). To test the hypothesis stated, the study employs structural equation modeling. This will help the researcher to examine the direct effect of financial budget and technology adaption of SMEs from the perspective of sustainability and big data. Results of the study stated that SMEs sustainability and big data are directly and positively related to the financial budget planning of technology-based SMEs. The study also found that big data plays an important role in the businesses, specifically for their own growth.